Improving the FAIRness of Japanese Archaeological Grey Literature - Takata, Yuichi; Yanase, Peter (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
In Japan, archaeology is predominantly an administrative pursuit, with only 15,261 research-driven excavations compared to 331,574 rescue excavations linked to development projects from 1976 to 2022. This approach operates within a broader framework focused on protecting archaeological sites, part of a larger cultural property preservation program governed by the Law for the Protection of Cultural Properties. The law emphasizes both the preservation and utilization of cultural properties, with protection encompassing these activities. Administrative tasks, including excavation, analysis, selection, repair, public sharing, museum display, and preservation, constitute a cyclical process of cultural property management. The decentralized administrative structure involves the national-level Agency for Cultural Affairs and local boards of education at prefectural and municipal levels. Notably, 95% of excavations over the past fifty years were conducted by administrative agencies as part of cultural property preservation. Fieldwork reports are considered the end-products of excavations, crucial for disseminating results and claiming common ownership. However, due to decentralization, the production and dissemination of grey literature in Japanese archaeology lack coherent management. Initiatives like the Comprehensive Database of Archaeological Site Reports in Japan (SORAN) aim to enhance the Findability, Accessibility, Interoperability, and Reusability (FAIRness) of Japanese archaeological grey literature.